Clinical outcomes of generic versus brand‐name clopidogrel for secondary prevention in patients with acute myocardial infarction: A nationwide cohort study - Cze Ci Chan; Ying‐Chang Tung; Kuang‐Tso Lee; Yi‐Hsin Chan; Pao‐Hsien Chu (Wiley, 2023)
Abstract Skepticism exists among healthcare workers and patients regarding the efficacy and safety of generic medication, despite its potential to lower healthcare costs. This study aimed to compare the outcomes of a generic clopidogrel and its brand‐name counterpart for secondary prevention in patients with acute myocardial infarction (AMI). Using the Taiwan National Health Insurance Research Database, we identified 49,325 patients who were hospitalized for AMI between January 1, 2008 and December 31, 2013 and prescribed either generic or brand‐name clopidogrel. Among them, 2419 (4.9%) were prescribed the generic clopidogrel. After propensity score matching, both the generic and brand‐name groups consisted of 2382 patients. The primary efficacy outcome was a composite of myocardial infarction, coronary revascularization, ischemic stroke, and all‐cause death. The primary safety outcome was major bleeding requiring hospitalization. At a mean follow‐up of 2.5 years, the generic and brand‐name clopidogrel groups had comparable risks of primary efficacy outcome (41.9% vs. 42%; hazard ratio [HR] 0.96; 95% confidence interval [CI] 0.88-1.04), and the risks of the individual components were also similar. There were no significant differences between the two groups in major bleeding (7.9% vs. 7.9%; HR 0.99; 95% CI 0.81-1.21). Subgroup analyses also revealed no statistically significant interactions between the treatment effect and various subgroups. In this retrospective database analysis, the generic clopidogrel was comparable to its brand‐name counterpart regarding cardiovascular and bleeding outcomes for the treatment of patients with AMI.